Study of Livestock Farmer's Satisfaction with Beef Cattle Insurance Program in Polewali Mandar Regency, West Sulawesi Province - Susanti S, Irma; Khaliq, Taufik Dunialam; Nuraliah, Siti (Jurnal AGRISEP, 2025)
This study aims to analyze the model of farmer satisfaction with the Asuransi Usaha Ternak Sapi (AUTS) program in Polewali Mandar Regency. This research was conducted in Polewali Mandar Regency in April-October 2024. This research model is quantitative descriptive research. The number of respondents in this study was 83 farmers. The data obtained were then processed and analyzed using Path Analysis. The results of the survey of the characteristics of beef cattle farmers in Polewali Mandar Regency include being dominated by men, aged 51-60 years, married, with a high school education level, an average monthly income of less than IDR 1,000,000, 6-10 years of farming, and having 0-5 beef cattle. The technical competence aspect has a significant effect on service quality, while social competence does not have a significant effect on service quality. The satisfaction model developed from technical, social and service quality competency factors has been proven to have a significant influence on the level of farmer satisfaction.. Service quality affects farmer satisfaction as participants in AUTS.